Mergers in the agribusiness sector: Theoretical analysis and empirical evidence from Greece - Pazarskis, Michail; Gkatziou, Maria; Kourtesi, Sofia; Kaitozhi, Zoi (International Journal of Applied Economics, Finance and Accounting, 2023)
Bigger and bigger companies are expanding their control over agriculture and food. Concentration processes with enormous dynamism are taking place at all stages of the supply chain. The trend is towards global players: companies are getting bigger through mergers and displacing the competition. Through their sales or purchasing policies, they are promoting a type of agriculture in which the focus is on increasing productivity and market share augmentation in the supply chain. The purpose of this research was to look into mergers that have occurred among companies in the agribusiness sector and provide useful insights from Greece. This study examined mergers in the agribusiness sector using a questionnaire distributed among employees of food companies and companies in food chains. The majority of the respondents had about five years of experience in the agribusiness sector and had a permanent position. The research results revealed that employees take a new wave of mergers in the agricultural sector for granted; however, they are concerned about how staff are dealt with and even layoffs. Finally, respondents claimed to be in favor of mergers to avoid the closure of yet more businesses but emphasized the importance of protecting workers’ rights.